IMPLEMENTASI MANAJEMENT PENDIDIKAN ISLAM BERBASIS INTEGRASI SALAF-MODERN DI PONDOK PESANTREN DARUL ISTIQOMAH NGUMPUL BALONG PONOROGO - Eko Iskandar; Ayoga Aditya Kurniawan; M. Zainal Arif; Rido Kurnianto (Universitas Muhammadiyah Ponorogo, 2024)
Islamic Education Management is education that aims at and develops an Islamic society, so that it can benefit other people. Islamic Education Management Based on Salaf_Modern Integration which is implemented at the Darul Istiqomah Islamic Boarding School is an integration of Salaf and Modern Education Management. The research was conducted with the aim of finding out the Implementation of Islamic Education Management Based on Salaf-Modern Integration. This research method uses qualitative research methods. Judging from the location of this research, it is a type of field research. This research is based on data collected directly from the field which aims to systematically describe the facts found in the research. Field research is intended to obtain data related to the discussion in this thesis. The researchers' findings after conducting initial observations at the Darul Istiqomah Islamic Boarding School found several things as follows: Firstly, curriculum planning at the Islamic boarding school was carried out by the Islamic boarding school itself with 3 stages, namely planning by the principal or director of education levels, then reporting to the Foundation section and discussing with the facilitator. . The two Islamic boarding school curricula through organizing take 3 curricula, namely the Pondok Salaf curriculum, the Pondok Modern Curriculum. Second, implementation is carried out by facilitators or teachers with supervision by the school principal and the Foundation department. The four evaluations are carried out weekly, semesterly, annually and incidentally involving the school administrators, facilitators/teachers, the curriculum department, and the Foundation. Implementation of Salah_Modern Integration is divided into 3 times, in the morning with modern subjects, in the afternoon activities with Salafiyah subjects and in the evening used to study Arabic and other languages